Problem based learning (PBL) vs. Case based curriculum in clinical clerkship, Internal Medicine innovated Curriculum, Student prospective - Aljarallah, Badr; Hassan, Mohammad Saleh (International Journal of Health Sciences, 2015)
Background. The vast majority of PBL experience is in basic science courses. Application of classic Problem based learning in clerkship phase is challenging. Although the clinical case is considered a problem, yet solving this problem following the burrow’s law has faced hurdles. The difficulties are facing the learner, the teacher and curricula. We implement innovative curriculum for the clerkship year in internal medicine course. Method. We surveyed the student just before coming to an internal medicine course to ask them about continuing PBL or other types of learning in clinical years. A committee was created to study the possible ways to integrate PBL in the course. After multiple brainstorming meeting, an innovated curriculum was implemented. Student surveyed again after they completed their course. The survey is asking them about what is the effect of the implemented curriculum in their skills, attitude, and knowledge. Results. 70% of Students, who finished their basic science in PBL, preferred not to have classical PBL, but more a clinical oriented case based curriculum in the clinical years. After this innovated curriculum, 50 -60 % of students who completed it showed a positive response in all aspects of effects including skill, attitude, and knowledge. The Innovated curriculum includes daily morning report, 3 bedside teaching, investigation session, and clinical reasoning weekly, and Lectures up to twice a week. Conclusion. We suggest implementing a curriculum with PBL and case-based criteria in clinical phase are feasible, we are providing a framework with this innovated curriculum. Key words: problem-based learning, learning strategies, medical education, problem solving, critical thinking, problem-based curriculum, case based curriculum, case based learning and clinical phase.